Perlindungan Hukum Terhadap Kerusakan Benda Cagar Budaya Di Aceh Utara - Nasir, Muhammad; Harun, Harun; Ayun, Siti Qurrata (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2023)
Cultural Heritage in North Aceh suffered destruction both intentionally and unintentionally. Its existence must be maintained to survive and avoid various threats that can speed up the weathering process. The management of cultural heritage problems is often neglected, this is because the people of Aceh do not understand the problem of cultural heritage. With the existence of legal protection, it is hoped that it will be able to preserve cultural heritage objects. The Aceh region has special autonomy and has Law No. 11 of 2006 concerning the Government of Aceh (UUPA). It is explained in article 149 that: "The Government of Aceh and the Regency/City Government are obliged to carry out integrated environmental management by paying attention to spatial planning, protecting biological natural resources, non-biological natural resources, artificial resources, conservation of biological natural resources and their ecosystems, cultural heritage, and biodiversity with due regard to the rights of indigenous peoples, and for the greatest extent for the welfare of the population." In Law Number 11 of 2010 Article 105 explains the Criminal Provisions for people who damage cultural heritage. Article 105 explains that "Any person who intentionally damages the Cultural Heritage as referred to in article 66 paragraph (1) shall be sentenced to a minimum imprisonment of 1 (one) year for a maximum of 15 (Fifteen) years and / or a fine of at least Rp. 500,000,000 ( Five Hundred Million Rupiah) and a maximum of Rp. 5,000,000,000 (Five Billion Rupiah)." The approach method used in this study is empirical juridical, namely legal research that obtains data from primary data. This type of research is descriptive research, namely to obtain a brief overview of a problem based on an applicable law and related to the problem to be discussed in a writing, then compile it logically and systematically. The results showed that legal protection against damage to cultural heritage objects in North Aceh is based on legal rules or norms, especially those listed in laws and regulations. The suggestion from this study is that the Government is expected to pay comprehensive attention to the protection of cultural heritage objects in North Aceh. The Government of North Aceh should form a qanun on the preservation of cultural heritage objects and to the people of Aceh it is hoped that they can maintain, care for and preserve cultural heritage objects and can become valuable heritage for the next community.